Environmental linguistics - do Couto, Hildo Honório (2019)
The main objetive of this article is to show that the majority of what is done under the name “ecolinguistics” is, in fact, envivonmental linguistics as defined here. This is because they deal with environmental, antienvironmental, pseudoenvironmental texts-discourses and similar subjects. In this case, essays that can be considered as belonging to “environmental linguistics” have been produced before the emergence of ecolinguistics itself, as can be seen in the three examples mentioned below. In other words, any essay dealing with environmental questions, using linguistic literature belong to environmental linguistics, even when the author is not a linguist. If the text dealing with environmental questions is written by a sociologist, it belongs to envivonmental sociology; if it is witten by a psychologist, it is envivonmental psychology, and soo on.